A prospective study of dysgeusia and related symptoms in patients with multiple myeloma after autologous hematopoietic cell transplantation. Issue 21 (30th August 2022) - Scordo, Michael; Shah, Gunjan L.; Adintori, Peter A.; Knezevic, Andrea; Devlin, Sean M.; Buchan, Marissa L.; Preston, Elaina V.; Lin, Andrew P.; Rodriguez, Natasia T.; Carino, Caroline A.; Nguyen, Linh K.; Sitner, Nancy Cruz; et al.
Abstract : Background: Dysgeusia is a common but understudied complication in patients undergoing autologous hematopoietic cell transplantation (auto‐HCT). We assessed the feasibility of using chemical gustometry (CG) to measure dysgeusia and explored its associations with symptom burden, nutrition, chemotherapy pharmacokinetics (PK), and the oral microbiome. Methods: We conducted a single‐center, prospective feasibility study (NCT03276481) of patients with multiple myeloma undergoing auto‐HCT. CG was performed longitudinally testing five flavors (sweet, sour, salty, bitter, umami) to calculate a total taste score (maximum score, 30). We measured caloric intake and patient‐reported symptoms, assessing their correlation with oral microbiota composition and salivary and blood melphalan PK exposure. Results: Among all 45 patients, 39 (87%) completed at least four (>60%) and 22 (49%) completed all six CG assessments. Median total CG scores remained stable over time but were lowest at day +7 (27, range 24–30) with recovery by day +100. Symptom burden was highest by day +10 (area under the curve, 2.9; range, 1.0–4.6) corresponding with the lowest median overall caloric intake (1624 kcal; range, 1345–2267). Higher serum/salivary melphalan levels correlated with higher patient‐reported dysgeusia and lower caloric intake. Oral microbiota α‐diversity was stable early and increased slightly by day +100. Conclusions: Assessment of dysgeusia by CG is feasible after auto‐HCT. Most dysgeusia, symptom burden, and lowest caloric intake occurred during the blood count nadir. Higher melphalan concentrations correlated with more dysgeusia and poorer caloric intake. Future studies will aim to modulate melphalan exposure by PK‐targeted dosing and characterize patient taste preferences to personalize diets for improved nutritional intake. Lay summary: Taste changes after cancer treatments are very common. We used chemical gustometry (taste testing) to study taste changes and to better understand why patients with multiple myeloma experience this symptom after autologous hematopoietic cell transplantation. We found that taste testing was feasible, taste changes peaked when blood counts were lowest, and most patients recovered their taste by 100 days after transplantation. Taste changes correlated with lower food intake and with higher levels of chemotherapy in the body. Future work will focus on using personalized chemotherapy doses to reduce taste changes and to match patients' individual taste preferences with their diets. Abstract : Chemical gustometry (taste testing) was feasible in patients with multiple myeloma undergoing autologous hematopoietic cell transplantation. Dysgeusia and symptom burden are highest and caloric intake is lowest during the blood count nadir but improved to near‐normal levels by three months after transplantation.